Dampak Modernisasi Terhadap Dinamika Kebudayaan Masyarakat di Indonesia - Ivana Theo Philia; Talita Sembiring; Ruth Yessika Siahaan; Dules Ery Pratama; M. Iqbal (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research discusses the impact of modernization on the dynamics of community culture in Indonesia and efforts to preserve cultural values ​​amidst the flow of change. The purpose of this study is to analyze the influence of modernization on social and cultural changes in society and to identify strategies that can be carried out to maintain the existence of local culture. The method used is a literature study with a qualitative approach, based on various scientific literature and secondary data. The results of the study indicate that modernization has positive impacts such as the development of science, changes in values ​​and attitudes that are more rational, and improvements in communication technology. However, modernization also contributes to the erosion of local cultural identity, especially among the younger generation who are more influenced by global culture. This study emphasizes the importance of cultural experience and cultural knowledge as preservation strategies, as well as the active role of families, schools, and communities in instilling cultural values ​​from an early age.